2020
DOI: 10.1186/s13578-020-00415-1
|View full text |Cite
|
Sign up to set email alerts
|

A three layered histone epigenetics in breast cancer metastasis

Abstract: Thanks to the advancement in science and technology and a significant number of cancer research programs being carried out throughout the world, the prevention, prognosis and treatment of breast cancer are improving with a positive and steady pace. However, a stern thoughtful attention is required for the metastatic breast cancer casesthe deadliest of all types of breast cancer, with a character of relapse even when treated. In an effort to explore the less travelled avenues, we summarize here studies underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 208 publications
(311 reference statements)
2
9
0
3
Order By: Relevance
“…We identified five EV associated proteins that were uniquely overrepresented in all three samples from the patient who responded to therapy relative to the non-responder (Table 3). Of these proteins, previous studies have shown that high expression of glyceraldehyde-3phosphate dehydrogenase, peroxiredoxin-2 and histone H2A type 2-A in breast cancer tissues are inversely correlated with overall survival and tumour aggressiveness [25][26][27][28]. Our own independent in silico analyses verified this observation (Supplementary Materials Figure S1).…”
Section: Discussionsupporting
confidence: 78%
“…We identified five EV associated proteins that were uniquely overrepresented in all three samples from the patient who responded to therapy relative to the non-responder (Table 3). Of these proteins, previous studies have shown that high expression of glyceraldehyde-3phosphate dehydrogenase, peroxiredoxin-2 and histone H2A type 2-A in breast cancer tissues are inversely correlated with overall survival and tumour aggressiveness [25][26][27][28]. Our own independent in silico analyses verified this observation (Supplementary Materials Figure S1).…”
Section: Discussionsupporting
confidence: 78%
“…This complex impacts transcription through interactions with histone acetyltransferases (HAT), followed by chromatin changes (Campbell et al, 2010). An increasing body of evidence reveals that histones' modifications (including methylation and acetylation) are involved in breast cancer metastasis (extensively reviewed in Nandy et al, 2020;Zhuang et al, 2020). According to Saramäki and others (Saramäki et al, 2009) both the histone acetylation and methylation processes are involved in cyclic chromatin looping during regulation of p21 expression after 1,25(OH) 2 D 3 supplementation to breast cancer cells.…”
Section: Possible Epigenetic Impact On Changes In Vitamin D Metabolism Observed In Breast Cancer Patientsmentioning
confidence: 99%
“…A further study has accessed the relationship between the SIRT1, H3k4ac, H3k9ac, and H4k16ac in different subtypes of breast cancer and found that SIRT1 is upregulated in luminal and HER2-enriched subtypes and significant downregulation in TNBC subtype while H3k4ac, H3k9ac, and H4k16ac were significantly reduced in luminal and HER2-enriched subtypes and relatively upregulated in TNBC subtype (Rifai et al, 2018). Meanwhile, the histone variants including GH2AX, MACROH2A.1, and H2Bub1 and histone chaperones such as APLF and HJURP were identified as the potential epigenetic biomarkers targeting specific subtypes of breast cancer (Nandy et al, 2020)…”
Section: Insight Into the Subtype-specific Associations Between Histomentioning
confidence: 99%